Volatility - Christodoulakis, George A. (Henry Stewart Talks, 2007)
Volatility is the most heavily used measure of risk in financial decision making, Discussion of validity of various measures of risk, Statement of conditions under which volatility is a good measure, Explanation of the empirical properties of data and their dynamics, Why models need to capture these characteristics, Analysis of various approaches of volatility estimation with particular emphasis on dynamic models in both univariate and multivariate contexts, Techniques for volatility model validation, Explanation of possible pitfalls, Out-of-sample volatility forecasting using dynamic models and various methods for volatility forecast evaluation
Archived at 2022/04/04